2017
DOI: 10.4172/2157-7587.1000268
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Land Use/Cover Dynamics and its Impact on the Low Flow of Gumara Watershed, Upper Blue Nile Basin, Ethiopia

Abstract: Land cover and Climate change are very important issues in terms of global context and their responses to environmental and socio-economic drivers. The dynamic of these two factors is currently affecting the environment in unbalanced way including watershed hydrology. In this paper the impact of land use/cover change on stream flow particularly on low flow were evaluated through application of the model Soil and Water Assessment Tool (SWAT) in Gumara watershed, Upper Blue Nile basin Ethiopia. The land use/cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…As a result, land use changes in the NRB, while minimal, could have still impacted the hydrological dynamics in the region. Furthermore, studies by [68,69] explain that land use changes can lead to declines in stream discharge in areas that are susceptible to low flows. The minimal LULC modifications could therefore signal an increase in human consumption along the course of the different stream segments, potentially leading to decreased streamflows as less water arrives to the HCDN gauges.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, land use changes in the NRB, while minimal, could have still impacted the hydrological dynamics in the region. Furthermore, studies by [68,69] explain that land use changes can lead to declines in stream discharge in areas that are susceptible to low flows. The minimal LULC modifications could therefore signal an increase in human consumption along the course of the different stream segments, potentially leading to decreased streamflows as less water arrives to the HCDN gauges.…”
Section: Discussionmentioning
confidence: 99%
“…So the impact of any disturbance will be minimal when catchments are of regional or larger scale. The dynamic of land use land cover is primary cause to altering the watershed hydrology (Chakilu and Moges 2017).…”
Section: Effects Of Land Use Land Cover On Soil Erosionmentioning
confidence: 99%
“…Land use land cover of the watershed is interesting character to explain the hydrological process of the watershed. The extent and rate of land use/cover change between 1973 and 2013 were studied by Chakilu and Moges (2017). Chakilu and Moges (2017); (Wubie et al 2016) reported that significant change of other land use (grass, bush and forestland) to cultivated land was observed.…”
Section: Land Use/cover Change and Hydrological Condition Of Gumara Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitive parameters which have significant influence on stream flow simulated by SWAT model were selected by sensitivity analysis process. Selected parameters are similar with the previous study done by [14]. The model efficiency was evaluated by using statistical variables determining the fitness of simulated stream flow with observed data.…”
Section: Swat Model Setup Calibration and Validationmentioning
confidence: 99%